A Review of Colin Lankshear’s and Michele Knobel’s Handbook for Teacher Research: From Design to Implementation - Catherine Compton-Lilly (Networks: An Online Journal for Teacher Research, 2006)
I have found a book that I have been seeking. Don’t be put off by its size and weight; this is a book that all teacher researchers will want to own. While written for teacher researchers, this book challenges us by refusing to stop at simple truisms about the importance of teacher’s voices and the benefits of reflective practice. This book challenges us not only to do teacher research, but to do it well.